Label-Free Measurements of Reaction Kinetics Using a Droplet-Based Optofluidic Device. (February 2015) - Mao, Zhangming; Guo, Feng; Xie, Yuliang; Zhao, Yanhui; Lapsley, Michael Ian; Wang, Lin; Mai, John D.; Costanzo, Francesco; Huang, Tony Jun
Label-free measurements of the reaction kinetics of a small sample volume are essential for efficient drug discovery, requiring methods and systems that are rapid, accurate, and cost-effective. Herein, we present an integrated optofluidic system for label-free characterization of reactions in a nanoliter reagent volume. This system contains a droplet-based microfluidic sampling section and an optical fiber–based spectroscopy detection section. By manipulating droplets containing reagents at certain concentrations at different times, quantifiable measurements via absorption spectroscopy can be made in a simple, sensitive, and high-throughput manner. We have demonstrated our system's capability by performing potency (IC50 ) assays of an inhibitor in a TEM-1 β-lactamase (enzyme) and nitrocefin (substrate) system. This integrated platform can potentially provide an automated, label-free, and low-cost method for many other assays of reaction kinetics.